Effect of konjac glucomannan (Kgm) on the reconstitution of the dermal environment against uvb-induced condition - Choi, Kyung Ho; Kim, Sung Tae; Bin, Bum Ho; Park, Phil June (Nutrients, 2020)
Skin layers serve as a barrier against unexpected critical changes in the body due to environmental factors. Excessive ultraviolet (UV) B exposure increases the levels of age-related factors, leading to senescent cells and damaged skin tissues. Widely used as a dietary supplement, konjac (Amorphophallus konjac) glucomannan (KGM) has shown skin regeneration potential in patch or sheet form with anti-inflammatory or immunosuppressive effects. However, the ability of KGM to reconstitute senescent/damaged skin following UV radiation has not been explored. Here, we demonstrate that KGM alleviates skin damage by increasing the proportion of young cell populations in UVB-exposed senescent human epidermal primary melanocytes. Young cell numbers increased depending on KGM dosage, but the senescent cells were not removed. Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot analysis showed that mRNA and protein levels of age-and pigmentation-related factors decreased in a manner dependent on the rate at which new cells were generated. Moreover, an analysis of mRNA and protein levels indicated that KGM facilitated youth by increasing cell proliferation in UVB-damaged human fibroblasts. Thus, KGM is a highly effective natural agent for maintaining skin homeostasis by promoting the reconstitution of the dermal environment against UVB-induced acute senescence or skin damage.
Keywords: Anti-Inflammatory Agents; Cell Proliferation; Cells, Cultured; Humans; Mannans; Skin; Skin Diseases; Ultraviolet Rays; Human embryonic fibroblasts; Human epidermal primary melanocytes; Konjac glucomannan; Senescence; Ultraviolet B